PENGARUH DOWN JOWNES ISLAMIC MARKET, INFLASI DAN STABILITAS POLITIK TERHADAP JAKARTA ISLAMIC INDEKX 70 - Habib, Muhammad Fauzan; Aziz, Roikhan Muhammad (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to analyze the influence of the Dow Jones Islamic Market World Index (DJII), inflation, and political stability on the Jakarta Islamic Index (JII). Using a quantitative approach with secondary data obtained from various sources, such as BPS, Bank Indonesia, OJK, and IDX, this study covers the time period from 2019 to 2023. The Partial Least Square (PLS) method was used to test the relationship between variables with the help of SmartPLS software version 3.0. The results showed that DJII and inflation do not have a significant influence on JII 70. DJII does not affect JII 70 due to differences in stock composition, different local economic conditions, and investment behavior between global and domestic markets. Meanwhile, inflation is also insignificant to JII 70 because most of the stocks in JII 70 come from sectors that are less sensitive to inflation. In contrast, political stability has a significant influence on the JII 70. Good political stability increases investor confidence and creates a safer investment environment, which in turn increases market liquidity and macroeconomic growth. The findings emphasize the importance of political factors in the analysis of Indonesia's Islamic stock market as well as the implications for investors and policy makers. This research provides important insights for investors in the Indonesian Islamic stock market to pay more attention to domestic factors such as political stability rather than relying solely on global indicators such as the DJII.